GREEN ECONOMY AND GREEN GROWTH AS A CONCEPTUAL BASIS FOR TRANSFORMING THE COMPETITIVENESS MANAGEMENT PARADIGM - MAISTRENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the conceptual significance of the green economy and green growth as interrelated components of a holistic paradigm for transforming the competitiveness management of the national economy in the context of sustainable development, European integration, and the aggravation of global environmental and climate challenges. The evolution of scientific approaches to interpreting the essence of the green economy and green growth is revealed, their key substantive characteristics are systematized, and their complementary nature within the modern paradigm of socio-economic development is substantiated. It is determined that the green economy serves as a target platform for transformations focused on preserving and accumulating natural capital, strengthening social inclusion, and ensuring environmental security. In contrast, green growth serves as a strategic tool for implementing this platform through a system of economic, institutional, and innovation mechanisms. It is substantiated that the transition to a green paradigm of competitiveness management entails a change in the logic of competitive advantage formation – from extensive resource use to resource efficiency, technological flexibility, and ecological innovation. The role of ESG principles, digitalization of environmental indicators, development of green markets, and low-carbon technologies in the formation of new criteria for assessing the competitiveness of economic systems is revealed. Qualitative features of the green economy are identified, reflecting its systemic nature, in particular, the integrative nature of resource flows, the ecologized cost structure, the reproducibility of the resource base, spatial equilibrium, and social inclusiveness of environmental changes. It is substantiated that the implementation of the principles of the green economy and green growth is a strategic prerequisite for increasing Ukraine's economic sustainability, energy security, and competitiveness in the context of post-war recovery and integration into the European economic space.
Keywords: green economy; green growth; competitiveness; sustainable development; environmental innovation; ESG principles